Statistical optimization of adsorption process fro removal of 2,4-dichlorophenol by activated carbon derived from empty fruit bunches - Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Toramae, Juria (2007)
The adsorption capacity of activated carbon produced from empty fruit bunches (EFB) through removal of 2,4-dichlorophenol from aqueous solution was carried out in the laboratory. The activated carbon was produced by thermal activation at 8000C with 30 minutes of activation time. The adsorption process conditions were determined with the statistical optimization followed by central composite design. A developed polynomial model for operating conditions of adsorption process indicated that the optimum conditions for maximum adsorption of phenolic compound were: agitation rate of 100 rpm, contact time of 8 hrs, initial adsorbate concentration of 250 mg/L and pH of 4. Adsorption isotherms and kinetics studies were conducted to evaluate biosorption process. Langmuir isotherm was more favorable (R2: 0.94) for removal of 2,4-dichlorophenol by the activated carbon produced rather than the Freundlich isotherm (R2: 0.88).